Dominant formation of h-BC2N in h-BxCyNz films: CVD synthesis and characterization - Seo, Tae Hoon; Lee, WonKi; Lee, Kyu Seung; Hwang, Jun Yeon; Son, Dong Ick; Ahn, Seokhoon; Cho, Hyunjin; Kim, Myung Jong (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Arranging carbon, boron, and nitrogen atoms in a sp(2) network can give rise to tunable electronic properties from insulators (h-BN) to metals (graphene). For semiconductor applications, the construction of a ternary structure (h-BxCyNz) is highly desirable, but its uniform and large-area synthesis has remained a great challenge. This challenge has been attempted by a facile chemical vapor deposition method with a single molecular precursor, N-tri-methyl borazine where boron, carbon, and nitrogen atoms are covalently bonded, onto Ni catalysts in conjunction with the quenching method after the synthesis. The atomic structure closely resembles h-BC2N as revealed by XPS (B:C:N similar to 1:1.8:1) and nanometer resolution EELS mapping, and the photoluminescence and electroluminescence observed from the h-BC2N film were in agreement, proving its well-established bandgap of 2.15 eV. As a practical application, the utilization of h-BC2N film for 2D light emitting diodes was demonstrated. Though films might have impurities such as small h-BN fragments and h-BxCyNz other than h-BC2N phase, we believe that this work provide a starting point of controlling the ternary BCN compounds that retain sp(2) hybridized chemical bonds. (C) 2021 Elsevier Ltd. All rights reserved.